Bypassing Equity? Transit Investment and Regional Transportation Planning. (March 2014) - Lowe, Kate
Regional planning may require a better understanding of multijurisdictional planning and equity within intergovernmental context. This research explores how intergovernmental context and metropolitan planning organization (MPO) activities impact rail proposals for low-income and minority communities. In two case studies, Boston and Miami, other government agencies determined the projects within MPO plans. In Boston, however, advocates leveraged agreements and federal rules to secure rail, and the MPO has developed extensive equity analyses. The cases exemplify the fiscal paradox that MPOs face—they have fiscally constrained plans but control little funding. Findings indicate the need to better relate multijurisdictional planning ambitions to intergovernmental context.